Toward the African Continental Free Trade Area : The Effects of Economic Integration and Democracy on Real Misalignments across Exchange Rate Regimes - Owoundi Fouda, Ferdinand; Avom, Desire; Kuete, Flora Yselle (World Bank, Washington, DC, 2021)
This paper evaluates the role of economic integration and democracy in rationalizing differences in real exchange rate misalignments across exchange rate regimes in Africa. To this end, the paper derives competing indexes of misalignment using modern cointegration techniques while accounting for cross-sectional dependence. The findings indicate that fixed regimes per se are not prone to more misalignments, as institutional quality and economic links with foreign partners critically matter in explaining the observed discrepancies. Furthermore, when distinguishing between African and international partners in investment agreements, the extent of misalignment differs according to the level of democracy, as democratic countries can afford intermediate regimes, while for weak democracies, fixed regimes are required to curb disequilibria. Finally, membership in a regional economic community significantly reduces the magnitude of misalignments. The results imply that the quality of institutions, more than the type of the exchange rate regime, is called into question and should be the focus of efforts ahead of successful implementation of the African Continental Free Trade Area.